Prognosis Risk of Urosepsis in Critical Care Medicine: A Prospective Observational Study. (3rd February 2016) - Qiang, Xin-Hua; Yu, Tie-Ou; Li, Yi-Nan; Zhou, Li-Xin
Abstract : This study aimed to investigate the clinical features of urosepsis and to raise awareness of this problem. Of the 112 sepsis patients enrolled, 36 were identified as having urosepsis. The bacteria involved in the infection leading to urosepsis included Escherichia coli, Proteus species, Enterococcus species, Klebsiella species, other Gram-positive cocci, and Pseudomonas aeruginosa . Although the organ/system dysfunction appeared earlier in the urosepsis patients than in the other sepsis patients (4.7 ± 2.4 versus 7.2 ± 4.5 hours, P < 0.001 ), the urosepsis patients presented with a better prognosis and lower 28-day mortality rate than the others (6% versus 37%). In the multivariate analysis, the type of sepsis (urosepsis, OR = 0.019, 95% CI = 0.001, 0.335, P = 0.007 ) and SOFA score (OR = 1.896, 95% CI = 1.012, 3.554, P = 0.046 ) remained significantly associated with the survival. The time of admission to the intensive care unit of 17 patients transferred from the Department of Urinary Surgery was significantly prolonged compared with those transferred from other departments (11.6 ± 7.3 versus 7.2 ± 4.9 hours, P < 0.05 ). In conclusion, urosepsis suggested a better prognosis, but attention needs to be paid in clinical practice, especially in urinary surgery.